A primary Ewing's sarcoma of the kidney: A case report and review of literature - Ornsinee Senkhum; Worapat Attawettayanon; Choosak Pripatnanont; Virote Chalieopanyarwong (Urology Annals, 2023)
Primary Ewing's kidney sarcoma is a rare and aggressive cancer with poor treatment outcomes. Furthermore, clinical presentations are nonspecific, such as abdominal pain, abdominal mass, cachexia, or hematuria. Currently, there is no consensus guideline for the treatment of this condition. We report on a 22-year-old man who presented with gross hematuria for 3 weeks. Computed tomography demonstrated a huge right renal mass with a thrombus in the inferior vena cava (IVC) without visceral metastasis. A percutaneous tissue biopsy revealed Ewing's sarcoma (ES) and the patient received neoadjuvant chemotherapy (doxorubicin and ifosfamide) for four cycles. This reduced the tumor's size significantly and made it eligible for surgical intervention. Radical nephrectomy and tumor thrombus removal with wedge IVC wall were performed. The final diagnosis of ES was confirmed by the immunohistochemistry of the kidney specimen. After a 5-year follow-up of the patient, clinical and imaging evidence demonstrated that there was no disease recurrence.